Heterometallic Metal-Organic Framework Based on [Cu4I4] and [Hf6O8] Clusters for Adsorption of Iodine - Hu, Huancheng; Chen, Fangyun; Zhang, Zhanyun; Liu, Dongcheng; Liang, Yuning; Chen, Zilu (Frontiers in Chemistry, 2022)
Heterometallic metal-organic framework (MOF) as a kind of porous materials is very important because of its excellent properties in catalysis, magnetic, sensor and adsorption fields, but the reasonable design and syntheses of them are still challenging. Herein we prepared one heterometallic MOF with the formula of [Hf6(μ3-OH)8(OH)8][(Cu4I4)(ina)4]2·22DMF (NS-1, ina = isonicotinate). Single-crystal X-ray diffraction analysis revealed that NS-1 is a three dimensional network with flu topology, constructing from 8-connected [Hf6(μ3-OH)8(OH)8]8+ and 4-connected [Cu4I4] clusters as second building units (SBUs). To our best knowledge, NS-1 is a rare example with two different metal clusters as SBUs in heterometallic Hf-based MOFs. Interestingly, NS-1 exhibits a reversible adsorption performance for iodine in the cyclohexane solution, the adsorption kinetics fits well with the pseudo-second-order equation, and Freundlich model relating to multilayer adsorption better describes the process of iodine absorption.